Perspectives on agroextractive activities in the Cerrado: Aldicir Scariot, João D'Angelis, Luís Carrazza e Sandra Afonso - Diniz, Janaína; Nogueira, Mônica (Sustainability in Debate, 2014)
Perspectives on agroextractive activities in the Cerrado: Aldicir Scariot, João D'Angelis, Luís Carrazza e Sandra Afonso